Divergent national-scale trends of microbial and animal biodiversity revealed across diverse temperate soil ecosystems - George, Paul B. L.; Lallias, Delphine; Creer, Simon; Seaton, Fiona M.; Kenny, John G.; Eccles, Richard M.; Griffiths, Robert I.; Lebron, Inma; Emmett, Bridget A.; Robinson, David A.; Jones, Davey L. (Nature communications, 2019)
Soil biota accounts for ~25% of global biodiversity and is vital to nutrient cycling and primary production. There is growing momentum to study total belowground biodiversity across large ecological scales to understand how habitat and soil properties shape belowground communities. Microbial and animal components of belowground communities follow divergent responses to soil properties and land use intensification; however, it is unclear whether this extends across heterogeneous ecosystems. Here, a national-scale metabarcoding analysis of 436 locations across 7 different temperate ecosystems shows that belowground animal and microbial (bacteria, archaea, fungi, and protists) richness follow divergent trends, whereas β-diversity does not. Animal richness is governed by intensive land use and unaffected by soil properties, while microbial richness was driven by environmental properties across land uses. Our findings demonstrate that established divergent patterns of belowground microbial and animal diversity are consistent across heterogeneous land uses and are detectable using a standardised metabarcoding approach. It is unclear whether microbes and animals residing in soils follow similar distribution patterns. Here, the authors report richness and diversity of soil microbes and invertebrates across soil, vegetation, and land use gradients in Wales, showing that land use affects animals while soil traits affect microbes.